Healthy Gadget Use Education to Support Children’s Personal and Social Development - Elpinaria Girsang; Yuliana Yuliana; Salsalina Yuniarty; Rizka Sulistyaningsih; Ipa Hariyati Malawat; Tiara Apriliani; Milawati Milawati (STAI Publisistik Thawalib Jakarta, 2026)
The problem in this activity is the low level of parents’ understanding regarding healthy gadget use, which can hinder the optimal social development of preschool-aged children. The purpose of this training is to improve parents’ knowledge about healthy gadget use to support children’s personal and social development. The training method used is interactive health education through lectures, group discussions, demonstrations, and participatory reflection with participating parents. The training results show a significant increase in parents’ knowledge of healthy, controlled gadget use for preschool children. Parents have a better understanding of the importance of limiting screen time, selecting age-appropriate content, and encouraging children to interact more with their social environment. In addition, there is a shift in parenting attitudes toward more informed, educational digital parenting practices, and children show improved social interaction, such as being more active in playing with peers and reduced gadget dependence. In conclusion, this training is effective in increasing parents’ knowledge and supporting children’s social development in a more optimal and balanced way. The significance of this training lies in its role as a preventive and promotive effort to improve the quality of family digital parenting in the modern technological era.